Fine thermohaline structure of the colombian pacific ocean (2004)
The present document shows strata classification of the Colombian Pacific Ocean - COLUMBIAN PACIFIC OCEAN, done by first time according its fine thermohaline structure, based on temperature and salinity fields analysis. Layers, where different mechanisms of fine structure predominate, were determined and everywhere in the area a stable stratification was observed, although conditions for not stability as a result of the double diffusion were present.